Assessing the Short-term Effect of Exchange Rate Liberalisation on Food Import Prices: The Regression Discontinuity in Time Employed for Russian Food Markets in 2014 - Loginova, Daria (Research on World Agricultural Economy, 2022)
This study summarises the main agricultural policies in Russia during 2014 and uses a sharp regression discontinuity design over time and data from the International Trade Centre to estimate the short-term effects of exchange rate liberalization in November 2014 on import prices in Russian food markets. The sharp regression discontinuity design over time allowed an export analysis of the short-term causal effects of the intervention on food import prices and distinguished the effect of exchange rate liberalisation between product groups and from other interventions without using data from control regions, products and suppliers. Significant upward shifts in import prices were found for pig products, fish and cheese. ER